Sargassum Sp. Sebagai Biokontrol Terhadap Kandungan Logam Berat Timbal (Pb) Yang Terserap Oleh Kerang Darah (Anadara granosa) [Sargassum Sp. As Biocontroll To Timbale (Pb) Heavy Metal Contens That Absorbed By Shell (Anadara granosa) ] - Mochammad Amin Alamsjah; Bagus Rakhmat; Yudi Cahyoko; Sudarno Sudarno (Jurnal Ilmiah Perikanan dan Kelautan, 2010)
Abstract Shell is aquatic organism class of Molluscs as non selective filter feeder and also as seafood main menu. In other side many food poisoning case was found as result consuming of Shell. Timbale (Pb) is one of very dangerous heavy metal and able to caused of poisoning in organism. According to PP RI Number 82/2001 Pb concentration that was suitable with maximum limit of aquatic quality is 0,03 ppm. Sargassum sp. also was knowned have been absorbing ability for heavy metal like Pb that spread in aquatic. Hopeable with a Sargassum sp. as biocontroll model on timbale heavy metal contens is able to prevent food poisoning causing contaminated shell consumtion. This research was done in Fisheries Laboratorium Fisheries and Marine Faculty Airlangga University on 15th – 11th 2010. The research method is experiment with design of experiment that used is Completely Randomized Design Factorial with three replicates (I, II and III) and consist of two factors, that is Pb(NO3)2 in concentration 0.015 ppm, 0.03 ppm and 0.06 ppm, Sargassum sp. in weight 100 g, 200 g and 400 g. Data analysis using Analysis of Variance (ANOVA), if there are any different it could be continued with Honestly Significant Difference (HSD) Test to known interaction between treatments. Result of the research indicates that Pb dose is significantly (p<0.05) to Pb contens number that absorp by Sargassum sp. among research. It's supported by HSD test indicates that highest result is A3 (Pb(NO3)2 0,06 ppm) that significantly with A2 (Pb(NO3)2 0,03 ppm) and A1 (Pb(NO3)2 0,015 ppm). Sargassum sp. is also be able to used as biocontroll to timbale heavy metal contens that absorbed by shell, because in low and highest dose Sargassum sp. absorption capacity to the timbale always bigger than shell absorption capacity . In other side, there are no interaction between timbale dose and weight of Sargassum sp. to timbale contens that absorbed by shell.